2020
DOI: 10.1002/jcla.23629
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles and clinical characteristics in primary Sjögren´s syndrome patient groups

Abstract: Background Primary Sjögren's syndrome (pSS) is an autoimmune disease characterized by a lymphocytic infiltrate in salivary glands driving to epithelial damage. The pSS patients present heterogenic clinical and serological characteristics. This heterogenicity could be due to the cytokine microenvironment. Cytokine levels have been analyzed and reported individually, showing controversial results; for that reason, we considered essential to evaluate a cluster of cytokines and relate them with antibody levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These cells can produce both Th1 and Th2 cytokines but are characterized by a shift in the favor of Th1 in the salivary gland in patients with SS ( Mitsias et al, 2002 ). Moreover, an overexpression of the cytokines IL4, IL17, and IFNγ have been associated with the pathogenesis of SS ( Verstappen et al, 2017 ; López-Villalobos et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These cells can produce both Th1 and Th2 cytokines but are characterized by a shift in the favor of Th1 in the salivary gland in patients with SS ( Mitsias et al, 2002 ). Moreover, an overexpression of the cytokines IL4, IL17, and IFNγ have been associated with the pathogenesis of SS ( Verstappen et al, 2017 ; López-Villalobos et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Serum containing unfavorable factors may even exacerbate ocular surface inflammation and lead to adverse effects when applied therapeutically. Some studies in the literature have demonstrated higher concentrations of serum inflammatory cytokines in patients with SS, especially when associated with a rheumatological disorder or during active disease (28,29,37,38). In a study by Ma et al (28), patients with SS were divided into active and inactive groups based on erythrocyte sedimentation rate and rheumatoid arthritis activity.…”
Section: Discussionmentioning
confidence: 99%
“… 105 Molecular markers might, in the future, provide key baseline information for pSS clustering. 42 , 45 , 106 …”
Section: Established Pssmentioning
confidence: 99%